2022
DOI: 10.1038/s41467-022-28165-3
|View full text |Cite
|
Sign up to set email alerts
|

Carbohydrate-aromatic interface and molecular architecture of lignocellulose

Abstract: Plant cell walls constitute the majority of lignocellulosic biomass and serve as a renewable resource of biomaterials and biofuel. Extensive interactions between polysaccharides and the aromatic polymer lignin make lignocellulose recalcitrant to enzymatic hydrolysis, but this polymer network remains poorly understood. Here we interrogate the nanoscale assembly of lignocellulosic components in plant stems using solid-state nuclear magnetic resonance and dynamic nuclear polarization approaches. We show that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
58
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 119 publications
(72 citation statements)
references
References 86 publications
3
58
1
Order By: Relevance
“…The 87.6 ppm signal has a similar chemical shift to the type-c cellulose recently identified in intact plant cell walls. 34 36 In plants, this special conformer belongs to some glucan chains that are deeply embedded in the core of a fibril, thus becoming spatially separated from surface chains. These chains cannot be accommodated by a small 18-chain microfibril; therefore, they might be created during the microfibril bundling process, which produces larger fibrils.…”
Section: Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The 87.6 ppm signal has a similar chemical shift to the type-c cellulose recently identified in intact plant cell walls. 34 36 In plants, this special conformer belongs to some glucan chains that are deeply embedded in the core of a fibril, thus becoming spatially separated from surface chains. These chains cannot be accommodated by a small 18-chain microfibril; therefore, they might be created during the microfibril bundling process, which produces larger fibrils.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Second, including the contribution of the weak peak at 87.6 ppm increased the content of interior cellulose to 35%. This minor component probably correlates with the type-c cellulose in plant cell walls, which belongs to a special form of glucan chains deeply embedded in the center of a bundle of microfibrils. , The increase in the surface-to-interior ratio might reflect the structural effect of the bundling of microfibrils. Third, including the area of the 81.5 ppm peak (likely from some highly disordered surface chains) in the calculation will bring down the percentage of interior cellulose back to 29%.…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The observation that p-hydroxybenzoylation correlates with xylan but not lignin nor cellulose contents could be an indication that lignin-bound pHB groups have an analogous role to xylan modifications. Indeed, it has been shown that lignin interacts primarily with xylan in poplar cell walls (Kirui et al, 2022), and it is known that lignin acylation impacts hydrophobicity and solubility by increasing the number of free phenolic groups (Lapierre et al, 2021). In addition, p-hydroxybenzoylation alters the structure of lignin by favouring β-aryl ether interunit linkages (Lu et al, 2015;Mottiar, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…The largest component within the plant cell wall is the secondary cell wall, made primarily from the polysaccharides cellulose (∼ 50%) and hemicellulose (∼ 20%), along with polyphenolic polymer lignin (∼ 30%) [4]. Emerging NMR evidence suggests that all three biopolymers form close interactions within the plant cell wall [5,6,7]. With an estimated global yield of 1.3 billion tons per year [8], these biomass components are an abundant and renewable bioeconomy feedstock for plant-based materials [4,9].…”
Section: Introductionmentioning
confidence: 99%